Empowering patients in chronic care to improve diabetes distress and glycaemic control: Protocol for a hybrid implementation‐effectiveness clinical trial. Issue 1 (18th November 2019) - Woodard, LeChauncy; Kamdar, Nipa; Hundt, Natalie; Gordon, Howard S.; Hertz, Brian; Amspoker, Amber B.; Kiefer, Lea; Mehta, Praveen; Odom, Edward; Rajan, Suja; Stone, Elizabeth; Jones, Lindsey; et al.
Abstract: Objectives: To evaluate the effectiveness of a collaborative goal‐setting intervention (Empowering Patients in Chronic Care [EPIC]) to improve glycaemic control and diabetesrelated distress, and implementation into routine care across multiple primary care clinics. Design: Randomized controlled trial comparing the effectiveness of the EPIC intervention with enhanced usual care (EUC) at five clinic sites located in the greater Chicago and Houston areas. We will measure differences in haemoglobin A1c (HbA1c ) and diabetes distress scale scores among study arms at post‐intervention and maintenance (6 months post‐intervention). We will evaluate implementation of the intervention across sites using the RE‐AIM framework. We will evaluate reach by comparing the per cent and characteristics of enrolled study participants among all potentially eligible participants in the given clinic population. Adoption is reflected by the characteristics of the involved providers and the number of intervention sessions conducted. Implementation of EPIC will be evaluated by number of sessions delivered, participants' evaluation of group sessions, and evaluation of quality of goal‐setting. Patients: We randomized 280 participants with equal allocation to EPIC and enhanced usual care (EUC). Results: At baseline, the groups were similar with the exception that EUC participants were more likely to have prior diabetes education. At baseline, participants were predominately older men who have poorly controlled diabetes (mean HbA1c = 76 mmol/mol [9.1%]) and moderate levels of diabetes distress (mean DDS = 2.43). Conclusions: This hybrid effectiveness‐implementation protocol is designed to accelerate the translation of a patient‐centred diabetes care intervention from research to clinical practice. Abstract : The Empowering Patients in Chronic Care (EPIC) intervention is an efficacious patient‐centred, goal‐oriented programme that combines group and individual approaches to help individuals with treated but uncontrolled diabetes reach their diabetic goals. The current trial is intended to examine EPIC as it transitions from laboratory setting into routine primary care.